(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Thalassaemia is a commonly occurring hereditary disorder. There is a high prevalence of thalassaemia disease in South-East Asia as well as Bangladesh. It is an autosomal recessive disorder, so consanguineous marriage is a very important factor for this disease. Mutated beta globin gene of haemoglobin from both parents is responsible for this disease to occur. But when the number of thalassaemia carriers is miserably high, then only avoidance of consanguineous marriage can’t prevent the birth of children with thalassaemia major. So, this cross sectional study was conducted among 120 diagnosed (by haemoglobin electrophoresis or high performance liquid chromatography) thalassaemia major patients in the Department of Haematology, Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2019 to May 2020. History from each patient was taken and blood samples were collected from their parents to confirm carrier state by haemoglobin electrophoresis. Blood samples were also collected from patients and their parents toperform complete blood count and peripheral Blood Film. This study showed the mean age of the participants was 15±9.34 and 73 (60.8%) patients were male and 47 (39.2%) were female. About, 71% of the study population lived in urban area, 81 (67%) patients were transfusion dependent thalassaemia patients. 15% thalas- saemia major patients had the history of consanguinity of their parents. Among the parents of the thalassaemia major patients, 62.5% were Beta thalassaemia trait (heterozygous state), 25.83% parents were Hb E trait ( heterozygous state), 7.08% parents were suffering from Beta Thalassaemia Major(homozygous state) and 11 (4.58%) parents were suffering from Hb E/Beta Thalassaemia which is a compound heterozygous state. Though consanguinity is a very influential factor, but the most important causative factor is the presence of high number of thalassaemia carrier in the population. So, it’s a burning issue for the nation to perform a routine carrier screening for all rather than focusing on consanguinity only, to lessen the burden of thalassaemia disease in Bangladesh. BSMMU J 2022; 15(1): 25-28